2020
DOI: 10.3389/fmicb.2020.566415
|View full text |Cite
|
Sign up to set email alerts
|

Core and Accessory Genome Comparison of Australian and International Strains of O157 Shiga Toxin-Producing Escherichia coli

Abstract: Shiga toxin-producing Escherichia coli (STEC) is a foodborne pathogen, and serotype O157:H7 is typically associated with severe disease. Australian STEC epidemiology differs from many other countries, as severe outbreaks and HUS cases appear to be more often associated with non-O157 serogroups. It is not known why Australian strains of O157 STEC might differ in virulence to international strains. Here we investigate the reduced virulence of Australian strains. Multiple genetic analyses were performed, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
2
4
0
Order By: Relevance
“…Three different virulence barcodes ( Table 2 ) were associated with O157:H7 with the majority being 06-00-1A-2C-00-00 ( n = 17) followed by 06-00-1A-00-00-00 ( n = 3) and 06-00-2A-00-00-00 ( n = 2). All O157:H7 isolates harboured a γ1 subtype eae consistent with previous reports ( Oswald et al, 2000 ; Blanco et al, 2005 ) and majority harboured stx 1a either alone or in combination with stx 2c, an stx genotype common in Australian STEC O157 ( Fegan and Desmarchelier, 2002 ; Mellor et al, 2012 , 2013 , 2015 ; Ingle et al, 2019 ; Pintara et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Three different virulence barcodes ( Table 2 ) were associated with O157:H7 with the majority being 06-00-1A-2C-00-00 ( n = 17) followed by 06-00-1A-00-00-00 ( n = 3) and 06-00-2A-00-00-00 ( n = 2). All O157:H7 isolates harboured a γ1 subtype eae consistent with previous reports ( Oswald et al, 2000 ; Blanco et al, 2005 ) and majority harboured stx 1a either alone or in combination with stx 2c, an stx genotype common in Australian STEC O157 ( Fegan and Desmarchelier, 2002 ; Mellor et al, 2012 , 2013 , 2015 ; Ingle et al, 2019 ; Pintara et al, 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…The predominant subtype detected in our dataset was Stx1a, which is known to be less cytotoxic than the subtypes Stx2a, Stx2d, and Stx2c ( Friedrich et al, 2002 ; Orth et al, 2007 ). Previous reports, albeit with a STEC O157:H7 bias, have also shown that Stx1a was the predominant Stx subtype circulating in Australia ( Mellor et al, 2012 , 2015 ; Ingle et al, 2019 ; Pintara et al, 2020 ). While the lower potency of Stx1a could explain the lower virulence of STEC in Australia, we would like to posit a possible genomic contributing factor to reduced virulence, at least in Stx1a-producing STEC.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We showed that within our dataset, STEC of lower pathogenic potential were in circulation. This observation is consistent with the trend previously observed at the pre-lockdown period, both at the national or the state level, which showed that most clinical STEC had lower pathogenic potential (17,(70)(71)(72)(73)(74)(75).…”
Section: Nsw Lockdown Dataset Indicated That Stec Of Lower Pathogenic...supporting
confidence: 92%
“…Whole genome sequencing was performed on the isolates listed in Supplementary Table S1 using the procedure described in our previous studies [14,15]. Briefly, DNA was prepared for sequencing using the Nextera XT kit (Illumina, San Diego, USA) and sequenced on the NextSeq500 using the NextSeq 500 Mid Output v2 kit (300 cycles) (Illumina), according to the manufacturer's instructions.…”
Section: Dna Library and Whole Genome Sequencingmentioning
confidence: 99%